Redesigning the SKK Website Using User-Centered Design and WEBUSE for Enhanced Usability - Kurnia Ramadhan Putra; Sofia Umaroh; Fauzi Yudianto (Jurnal Nasional Teknologi dan Sistem Informasi, 2025)
The Student Credit System (SKK) website plays a crucial role in managing students' extracurricular activities. However, usability issues in its previous design, such as inconsistent color schemes, confusing document uploads, unclear information tables, and unintuitive workflows, hindered user experience. This study aims to enhance usability and user satisfaction through a redesign using the User-Centered Design (UCD) method. The UCD methodology follows four structured stages: Specify the Context of Use, Specify User and Organization Requirements, Produce Design Solutions, and Evaluate Design Against User Requirements. To assess usability improvements, an evaluation was conducted using Website Usability Evaluation (WEBUSE), measuring four key aspects: Content, Organization, and Readability, Navigation and Links, User Interface Design, and Performance and Effectiveness. The results indicate substantial improvements. Usability scores increased from 0.45 to 0.93 for Content Organization, and Readability, 0.46 to 0.92 for Navigation and Links, 0.39 to 0.97 for User Interface Design, and 0.62 to 0.91 for Performance and Effectiveness, all reaching excellent usability levels. User feedback confirmed a more intuitive, visually cohesive, and user-friendly experience, enhancing accessibility and efficiency in managing SKK activities. In conclusion, applying UCD effectively enhances usability, validated by WEBUSE evaluation and user feedback. Despite these improvements, the study is currently limited to a Figma-based prototype, requiring further development for full implementation and real-world validation.